Setting up and running a small fruit or vegetable processing enterprise - Axtell, Barrie; Fellows, Peter (Technical Centre for Agricultural and Rural Cooperation, 2008)
If you are interested in starting up a business, food processing offers an excellent opportunity to generate income using locally available resources. Focusing on the establishment of such a business using fruits and vegetables, this detailed and informative manual covers topics such as: products and processes (bottling, drying and picking), potential markets, equipment, facilities and quality assurance. Issues involved in the mangagement of your business – health and safety, staffing issues, finances and business strategy – are also addressed in an easy-to-follow, practical way. The result of collaboration between small business owners and advisers, this text provides an invaluable resource to both start-up enterprises and established entrepreneurs who wish to update and improve their businesses and profitablility. The guide should be read along with volume 1 in the series (see 1041), which introduces aspects such as technical know-how, business skills and customer care.